Semiotic Elements of Barthes Model on Wall’s Ice Cream Advertisement - Halim, Farhatunisa Aulia Sultan; Andang Saehu; R. Myrna Nur Sakinah (Universitas Veteran Bangun Nusantara, 2024)
Wall’s ice cream advertisements contain various semiotic elements that can be analyzed linguistically and visually. Despite the extensive use of semiotics in advertising, limited research focuses on the application of Barthes’ semiotic model in food product advertisements. This study aims to identify and analyze the semiotic elements found in Wall’s ice cream advertisements using Roland Barthes’ framework, which classifies semiotic elements into denotation, connotation, and myth. A descriptive qualitative method is employed, with data sourced from advertisements on digital platforms such as Instagram and Pinterest. The analysis follows Barthes’ Order of Signification to examine how verbal and non-verbal signs construct layered meanings. The results show that the advertisements contain all levels of Barthesian semiotics, with Signifier and Connotative Signifier elements dominating. These findings provide insights into how Wall’s advertisements evoke emotions and cultural narratives, offering valuable guidance for future research on semiotics in advertising.